KNDy (Kisspeptin/Neurokinin B/Dynorphin) Neurons Are Activated during Both Pulsatile and Surge Secretion of LH in the Ewe - Merkley, Christina M. (Endocrine Society, 2012)
KNDy (kisspeptin/neurokinin B/dynorphin) neurons of the arcuate nucleus (ARC) appear to mediate the negative feedback actions of estradiol and are thought to be key regulators of pulsatile LH secretion. In the ewe, KNDy neurons may also be involved with the positive feedback actions of estradiol (E(2)) to induce the LH surge, but the role of kisspeptin neurons in the preoptic area (POA) remains unclear. The goal of this study was to identify which population(s) of kisspeptin neurons is (are) activated during the LH surge and in response to the removal of E(2)-negative feedback, using Fos as an index of neuronal activation. Dual-label immunocytochemistry for kisspeptin and Fos was performed on sections containing the ARC and POA from ewes during the luteal phase of the estrous cycle, or before or after the onset of the LH surge (experiment 1), and from ovary-intact, short-term (24 h) and long-term (>30 d) ovariectomized (OVX) ewes in anestrus (experiment 2). The percentage of kisspeptin neurons expressing Fos in both the ARC and POA was significantly higher during the LH surge. In contrast, the percentage of kisspeptin/Fos colocalization was significantly increased in the ARC, but not POA, after both short- and long-term E(2) withdrawal. Thus, POA kisspeptin neurons in the sheep are activated during, and appear to contribute to, E(2)-positive feedback, whereas ARC kisspeptin (KNDy) neurons are activated during both surge and pulsatile modes of secretion and likely play a role in mediating both positive and negative feedback actions of E(2) on GnRH secretion in the ewe.